Gadget Sebagai Agen Sosialisasi Baru dalam Keluarga Postmodern: Balita di Era Digital - Deska Fitriyani; Ainul Zulqoifah Asmawati; Yuanita Dwi Hapsari; Nabila Tahira (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This article examines the role of gadgets as new agents of socialization in postmodern families, with a particular focus on toddlers in the digital era. Using a literature study approach, the research systematically reviews findings from academic articles, research reports, and relevant studies published within the last five years. The unit of analysis is toddlers’ interaction with gadgets in the context of postmodern families, which are viewed as new social spaces where values, norms, and behaviors are formed. The research population consists of scholarly literature on gadget use in early childhood during the digital era, while the sample was selected based on inclusion criteria, namely relevance to family socialization, the role of technology in parenting, and its impact on toddlers’ development. The findings indicate that gadgets function not only as entertainment devices but also as agents of socialization that shape communication patterns, interaction, as well as cognitive and social development. However, gadgets bring dual implications: they provide opportunities for developmental stimulation yet also pose risks of reduced face-to-face interactions with parents. Therefore, postmodern families must adopt adaptive parenting strategies that balance gadget use with conventional social interactions.